Deep Eutectic Solvent Based Quechers Method for Green Extraction - Indriyanti Ibrahim; Rury Eryna Putri (Chemical Engineering Journal Storage (CEJS), 2025)
The trend of contaminant analysis methods is beginning to shift towards methods that are considered greener in an effort to support environmental sustainability. QuEChERS is known as a green extraction method because it requires less organic solvent and shorter pretreatment time than other conventional extraction methods. Deep Eutectic Solvent (DES) as a more environmentally friendly solvent has been developed to support the realization of green extraction. However, the use of DES specifically for the QuEChERS method has not been extensively investigated. Thus, the feasibility of using DES in the QuEChERS method has not been well elucidated. To fill this gap, this paper was prepared to provide an overview of the effectiveness of DES in the QuEChERS method. DES is known to act as an extractant and sorbent modifier. Recent advances in the use of DES based on the QuEChERS method, particularly in the extraction of pesticides, are discussed and future research needs related to its use on more complex matrices - such as biological matrices - are identified. In general, it is concluded that the use of DES based on the QuEChERS method is superior to extraction using synthetic organic solvents and fulfills the criteria of green chemistry.